An Interview with Serpil Altın and Korhan Uğur on Sustainable Cinema and Green Filmmaking: “Use the Earth Right So You Don’t Go Under” - Cansu Öksüz Karademir (Filmvisio)
In this interview, the concept of sustainability, which we have started to encounter frequently in daily life, is evaluated within the context of the Turkish film industry. Given the global influence of the Hollywood film industry, it is extremely important to raise awareness about sustainable practices in cinema and the necessary steps to ensure this awareness in future productions. Although studies and platformsrelated to sustainability have already been established in the film industries of the American and European continents, it appears that efforts in this direction within Turkish cinema are still in their initial stages. In this regard, an interview is conducted with Serpil Altın, the director of Turkey’s first feature-length sustainable film production Once Upon a Time Will Come: 2121, and co-producer Korhan Uğur. The discussion not only covers their experiences during the film’s production process and the details of green filmmaking but also includes a comparison between international efforts and similar initiatives within Turkish cinema. From this perspective, Once Upon a Time Will Come: 2121 can be considered a feature-length case study on green filmmaking efforts in Turkish cinema. The interview presents several examples of sustainable filmmaking and green filmmaking practices based on the film’s production process, along with recommendations for advancing such initiatives in the Turkish film industry. Thus, the interview aims to serve as a guide for these initiatives.